NEW HOST RECORD OF THE YELLOW STEAM BORER MOTHS, SCIRPOPHAGA INCERTDAS SHALL (LEPIDOPTERA: PYRALIDAE) - Sutrisno, Hari (JURNAL BIOLOGI INDONESIA, 2007)
SHORT COMUNICATIONNew Host Record of The Yellow Steam Borer Moths, Scirpophagaincertdas Shall (Lepidoptera: Pyralidae)